The Influence of Promotion and Service Quality on Customers' Decisions to Save at PT Bank Negara Indonesia, Balige Branch - Jopinus Ramli Saragih; Mhd Ramadhan; Anju Bherna D Nainggolan; Novika Br Pandia (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the influence of promotion and service quality on customer decisions to save at Bank Negara Indonesia (Persero) Tbk Balige Branch, both partially and simultaneously. This type of research is quantitative with a survey approach. The research sample consisted of 50 respondents taken from a population of 100 customers. Primary data were collected through questionnaires, while data analysis was carried out using validity and reliability tests, t-tests, F-tests, and multiple linear regression analysis with the help of SPSS software. The results showed that the promotion variable had no significant effect on customer decisions to save, while the service quality variable had a positive and significant effect on customer decisions. Simultaneously, promotion and service quality together had a significant effect on customer decisions to save at BNI Balige Branch. These findings emphasize the importance of consistently improving service quality in building customer trust and loyalty, as well as the need for innovation in promotional strategies to more effectively attract public interest in saving.